Pengaruh Penerimaan Dana ZISWAF, BOPO, dan Laba/Rugi Non Operasional terhadap Pendapatan Mudharabah dengan Firm Size Sebagai Variabel Moderasi Pada Perbankan Syariah di Indonesia Tahun 2018-2023 - Azkia, Arina; Budianto, Eka Wahyu Hestya (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2024)
This study was conducted with the aim of finding the effect of ZISWAF fund revenue, BOPO, and non-operating profit/loss on mudharabah income with firm size as a moderating variable in Islamic banking in Indonesia. This study uses a sample of financial sector companies included in the list of the Indonesia Stock Exchange (IDX) in 2018-2023. With the data contained is secondary data derived from quarterly reports accessed through the relevant company website. The purpose sampling technique was used to sample 115 companies for 5 years. The analysis method used is Panel Data Regression and Moderation Regression Analysis (MRA), all using Eviews 12. The results showed that the receipt of ZISWAF funds can increase mudharabah income due to increased equity and Islamic banking profits. In carrying out its operations, the BOPO variable is used to measure the effectiveness and ability of the bank, which can affect mudharabah income. Non-operating profit/loss can affect mudharabah income positively or negatively. And mudharabah income in Islamic banking in Indonesia can be influenced by firm size variables.